Knowing skilling in contemporary public administration - Hess, Michael; Adams, David (2002)
Knowledge is the latest-buzzword in public administration, yet contemporary debates demonstrate a poor understanding of how knowledge is constructed and valued and of how public administration knowledge frames are changing in response to major structural shifts in political imperatives. In particular the retreat from economic rationalism and the embracing of social and human capital ideas with the search for `third ways' and `triple bottom lines' are bringing more constructivist knowledge frames back into plays. In this way centralised `rational/expert' knowledge is being challenged by knowledge arising from cooperative, local inquiry and multiple knowledge frames are now being brought to bear in public administration. Yet public administration, as a profession, seems unsure of whether this is an elegant finesse implying little real change or an exposure of the naked pretension of previously dominant unitary frameworks. This article uses a historical comparison to show how changes in the ontology and epistemology of public administration are demanding new skills of contemporary public administrators. - Reproduced.
Keywords: Public administration